Advances in accounting education teaching and curriculum innovations - Feldmann, Dorothy; Rupert, Timothy J. (Emerald, 2012)
Advances in Accounting Education: Teaching and Curriculum Innovations publishes a wide variety of articles dealing with accounting education at the college and university level. FPpers oftencinclude Thought pieces that share anecdotal experiences with various pedagogical tools. Position papers on particular issues; Comprehensive literature reviews grounded in theory; Conceptual models; Historical discussions with implications for current and future pedagogical efforts; Methodology discussions and Research studies with implications for improving accounting education.
Keywords: Accounting.; Accounting -- Study and teaching (Higher); Educational innovations.; elektronické knihy; electronic books